FIRST PAGES OF PERUVIAN LAW - Walter Salvador Galvez Condori (2019)
Writing about Toribio Pacheco is certainly describing one of the roots of Peruvian law and, in turn, a wonderful way to recall historical aspects of the life of Peru; perceiving the Dantesque legacy of those who barely encrypted their 40s, undertook their journey to the celestial field. To point out that he was an illustrious jurist, prominent diplomat, politician and distinguished journalist is insufficient; therefore, the love for his homeland and the impetuous struggle for the progress of our country, as well as the insatiable and continuous aspiration for knowledge became the constitution of a being with a superior culture, which was hardly appreciated in his time and even in the present times and that in these lines, we look with admiration to recognize it.